Bayesian hypothesis testing for pattern discrimination in brain decoding - Olivetti, Emanuele; Veeramachaneni, Sriharsha; Nowakowska, Ewa (Pattern recognition, 2012)
Research in cognitive neuroscience and in brain–computer interfaces (BCI) is frequently concerned with finding evidence that a given brain area processes, or encodes, given stimuli. Experiments based on neuroimaging techniques consist of a stimulation protocol presented to a subject while his or her brain activity is being recorded. The question is then whether there is enough evidence of brain activity related to the stimuli within the recorded data. Finding a link between brain activity and stimuli has recently been proposed as a classification task, called brain decoding. A classifier that can accurately predict which stimuli were presented to the subject provides support for a positive answer to the question. However, it is only the answer for a given data set and the question still remains whether it is a general rule that will apply also to new data. In this paper we try to reliably answer the neuroscientific question about the presence of a significant link between brain activity and stimuli once we have the classification results. The proposed method is based on a Beta-Binomial model for the population of generalization errors of classifiers from multi-subject studies within the Bayesian hypothesis testing framework. We present an application on nine brain decoding investigations from a real functional magnetic resonance imaging (fMRI) experiment about the relation between mental calculation and eye movements. ► Population inference from brain decoding studies relies on classical hypothesis testing and a set of approximations. ► A more accurate statistical test is proposed within the Bayesian hypothesis testing framework. ► The test is based on a hierarchical Beta-Binomial model linking the observed number of errors of each subject-specific classifier to the population parameters. ► An efficient algorithm to evaluate the test is provided. ► An application is presented on an fMRI study about the relation between mental calculation and eye movements.